+0  
 
0
142
1
avatar

if f(x)=2x^2-3 and g(x)=x-2 find f(g(3) 

Guest May 11, 2018
 #1
avatar+7266 
+1

To find  f( g(3) ) , first let's find  g(3) .

 

g(x)  =  x - 2_____ Plug in  3  for  x
g(3)  =  3 - 2 Simplify.
g(3)  =  1  

 

Since  g(3) = 1 ,  we can substitute  1  in for  g(3) .

 

f( g(3) )  =  f( 1 )

 

Now we just have to find  f(1) .

 

f(x)  =  2x2 - 3_____ Plug in  1  for  x
f(1)  =  2(1)2 - 3 Simplify.
f(1)  =  2(1) - 3  
f(1)  =  2 - 3  
f(1)  =  -1  

 

So....

 

f( g(3) )  =  f(1)  =  -1

 

f( g(3) )  =  -1

hectictar  May 11, 2018

17 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.